Hubungan Pengetahuan dan Dukungan Keluarga terhadap Kegiatan Posyandu Lansia - Keumalahayati Keumalahayati; T Alamsyah (Jurnal Keperawatan, 2018)
The Elderly Posyandu is a social organization that is engaged in fostering advanced health, health workers who serve elderly health and the wider community are a forum for the community supported by cross-sectoral collaboration. The purpose of this study was to determine the relationship between knowledge and family support for elderly Posyandu activities in Seuriget Village, Langsa Barat District, Langsa City in 2014. The research method used a crossectional research design. The population of this study was all usas aged 60-69 years totaling 79 people. The sample in this study was total sampling. The research instrument used was a questionnaire. The results of the study showed that 88.6% of respondents did not take part in the elderly posyandu activities, 72.2% of respondents were less knowledgeable and the majority of family support was 74.7%. The chi-square test results showed knowledge with the elderly posyandu activities (p = 0.001), with a value of X2 count = 12,443> X2 = 3.841. There was a relationship between family support and elderly posyandu activities (p = 0.007) and the value X2 count = 9.069> X2 = 3.841. Suggestions for the results of the study can be input for the community and the elderly towards the importance of the elderly Posyandu and can be used as input for the research site on the importance of the elderly posyandu.